Blended Learning Method Using Google Classroom: Improving Students’ Conceptual Knowledge - Rizki Fadilah; Aisyah, Aisyah; Evitamala Siregar (PT Inovasi Pratama Internasional, 2025)
The demand for the integration of technology to improve the quality of education in the 21st century, in order to achieve innovative leaning and enchance students’ understanding of subject, serves as the background of this study. The aim of this research is to examine the relationship between the Blended Learning method using Google Classroom and students’ conceptual knowledge ability. The population of this study consists of XI-1th-grade students at SMA Negeri 1 Siabu, Mandailing Natal Regency. The sampling method used in this study is purposive sampling, selecting 30 students froms class XI-1 as the research sample. The instruments used in this study are test questions and questionnaries. The data analysis technique employer is correlationa analysis with prerequisite testing. The results of study show a very strong positive relationship between Blended Learning using Google Classroom and students conceptual knowledge, as indicated by mulitiple correlation coefficient (R) of 0.9935 and a determination coefficient of 98.65%.